Measuring norms and beliefs about gender-based violence among adolescent girls and young women in rural Senegal: Psychometric validation in a novel population and setting - Heckert, Jessica; Dione, Malick; Hidrobo, Melissa; Peterman, Amber; Le Port, Agnes; Seye, Moustapha (International Food Policy Research Institute, 2025)
Intimate partner violence (IPV) and non-partner sexual violence (NPSV) are forms of gender-based violence (GBV) and contribute to a range of poor mental and physical health outcomes (Beydoun et al., 2012; Dillon et al., 2013; Flor et al., 2025). Among ever-partnered women aged 15 and older in the Africa region, 33% report physical and/or sexual IPV in their lifetime and 19% in the past year (Sardinha et al., 2022). In addition, the lifetime prevalence of NPSV among woman aged 15 to 49 years is 6% in sub-Saharan Africa (Sardinha et al., 2024). Norms (i.e., the societal expectations and rules that dictate acceptable behavior in a given context) that consider GBV acceptable in its various forms perpetuate GBV by reinforcing its acceptability. Among interventions that aim to reduce the prevalence of GBV, many aim to do so, at least in part, by changing both norms and beliefs about GBV (Leight et al., 2023; Ullman et al., 2025). Validated scales for measuring these outcomes are limited, but important for understanding factors that contribute to changes in norms and beliefs.